Quintic vertices of spin 3, vector and scalar fields - Lavrov, Peter M. (Physics Letters B)
As a result of special deformations of free gauge models of massless spin 3, massive vector and real scalar fields, quintic vertices within new approach Buchbinder and Lavrov (2021) [32]; Buchbinder and Lavrov (2021) [33]; Lavrov (2022) [34] are constructed. They are described by local functionals which are invariant under original gauge transformations.